A modified relief of unilateral ureteral obstruction model. (1st January 2019) - Song, Jie; Liu, Jing; Luo, Jia; Zhang, Qingyan; Xia, Yangyang; Shao, Qiuyuan; Sun, Cheng; Jiang, Chunming; Zhang, Miao; Zhu, Wei
Abstract: Objectives: To improve the mouse model of relief for unilateral ureteral obstruction (RUUO) and explore the pathological process of renal fibrosis after the obstruction was relieved. Methods: C57BL/6 mice in model group were randomly divided into RUUO group, improved RUUO group, and UUO group. After leaving Unilateral Ureteral Obstruction (UUO) for 3 days, the obstruction was released by reimplantation way in RUUO group and in reimplantation + catheter way in improved RUUO group. C57BL/6 mice in observation group were randomly divided into 1d RUUO group, 3d RUUO group, 7d RUUO group, and 14d RUUO group. Three days after UUO, the obstruction was released by reimplantation + catheter in four groups. We detected the renal volume, H&E, Masson staining, and immunohistochemistry of kidney pathology on the seventh day after RUUO in model group and on the 1st, 3rd, 7th, and 14th day after RUUO in observation group. Results: Comparing with mice in RUUO group, mice in improved RUUO group had lower renal volume, tubular damage score, and collagen area percentage. After the obstruction was relieved, the renal volume decreased gradually within 2 weeks. The tubular damage score in 7d RUUO group was lower than that in 1d RUUO and 3d RUUO group. However, the tubular damage score in 14d RUUO group was higher than that in 7d RUUO group. The tendency of collagen area percentage and α-SMA IOD value were consistent with the tubular damage score. Conclusions: Using the method of reimplantation + catheter, a reliable mice model of RUUO can be got. After RUUO, the de-obstructed kidneys are still in damage and fibrosis state.